Reactive electron scattering from biomolecules and technologically relevant molecules - Matias, Carolina Raquel Guedes (2015)
The role of a set of gases relevant within the context of biomolecules and technologically relevant molecules under the interaction of low-energy electrons was studied in an effort to contribute to the understanding of the underlying processes yielding negative ion formation. The results are relevant within the context of damage to living material exposed to energetic radiation, to the role of dopants in the ion-molecule chemistry processes, to Electron Beam Induced Deposition (EBID) and Ion Beam Induced Deposition (IBID) techniques. The research described in this thesis addresses dissociative electron attachment (DEA) and electron transfer studies involving experimental setups from the University of Innsbruck, Austria and Universidade Nova de Lisboa, Portugal, respectively. This thesis presents DEA studies, obtained by a double focusing mass spectrometer, of dimethyl disulphide (C2H6S2), two isomers, enflurane and isoflurane (C3F5Cl5) and two chlorinated ethanes, pentachloroethane (C2HCl5) and hexachloroethane (C2Cl6), along with quantum chemical calculations providing information on the molecular orbitals as well as thermochemical thresholds of anion formation for enflurane, isoflurane, pentachloroethane and hexachloroethane. The experiments represent the most accurate DEA studies to these molecules, with significant differences from previous work reported in the literature. As far as electron transfer studies are concerned, negative ion formation in collisions of neutral potassium atoms with N1 and N3 methylated pyrimidine molecules were obtained by time-of-flight mass spectrometry (TOF). The results obtained allowed to propose concerted mechanisms for site and bond selective excision of bonds.